GWAS on retinal vasculometry phenotypes - Jiang, Xiaofan; Hysi, Pirro G.; Khawaja, Anthony P.; Mahroo, Omar A.; Xu, Zihe; Hammond, Christopher J.; Foster, Paul J.; Welikala, Roshan A.; Barman, Sarah A.; Whincup, Peter H.; Rudnicka, Alicja R.; Owen, Christopher G.; et al. (PLoS genetics, 2023)
The eye is the window through which light is transmitted and visual sensory signalling originates. It is also a window through which elements of the cardiovascular and nervous systems can be directly inspected, using ophthalmoscopy or retinal imaging. Measurements of ocular parameters may therefore offer important information on the physiology and homeostasis of these two important systems. Here we report the results of a genetic characterisation of retinal vasculature. Four genome-wide association studies performed on different aspects of retinal vasculometry phenotypes, such as arteriolar and venular tortuosity and width, found significant similarities between retinal vascular characteristics and cardiometabolic health. Our analyses identified 119 different regions of association with traits of retinal vasculature, including 89 loci associated arteriolar tortuosity, the strongest of which was rs35131825 ( p = 2.00×10 −108 ), 2 loci with arteriolar width (rs12969347, p = 3.30×10 −09 and rs5442, p = 1.9E-15), 17 other loci associated with venular tortuosity and 11 novel associations with venular width. Our causal inference analyses also found that factors linked to arteriolar tortuosity cause elevated diastolic blood pressure and not vice versa.